2013
DOI: 10.1155/2013/712303
|View full text |Cite
|
Sign up to set email alerts
|

Sargachromenol from Sargassum micracanthum Inhibits the Lipopolysaccharide‐Induced Production of Inflammatory Mediators in RAW 264.7 Macrophages

Abstract: During our ongoing screening program designed to determine the anti-inflammatory potential of natural compounds, we isolated sargachromenol from Sargassum micracanthum. In the present study, we investigated the anti-inflammatory effects of sargachromenol on lipopolysaccharide (LPS)-induced inflammation in murine RAW 264.7 macrophage cells and the underlying mechanisms. Sargachromenol significantly inhibited the LPS-induced production of nitric oxide (NO) and prostaglandin E2 (PGE2) in a dose-dependent manner. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Normal inflammatory responses are tightly controlled and self-limiting. Chronic inflammation, however, can lead to an abnormal increase in osteoclastic bone resorption and excessive bone destruction as observed in osteoporosis, rheumatoid arthritis, and periodontal disease (PD) [ 1 3 ]. Osteoclasts are multinucleated cells which are capable of degrading bone matrix and play an important role in physiological bone development and remodeling [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Normal inflammatory responses are tightly controlled and self-limiting. Chronic inflammation, however, can lead to an abnormal increase in osteoclastic bone resorption and excessive bone destruction as observed in osteoporosis, rheumatoid arthritis, and periodontal disease (PD) [ 1 3 ]. Osteoclasts are multinucleated cells which are capable of degrading bone matrix and play an important role in physiological bone development and remodeling [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies using isolated sargachromenol from different sources confirmed the results obtained by Kim et al For instance, sargachromanol isolated from the marine brown alga Sargassum serratifolium inhibited peroxinitrite anion-mediated albumin nitration with an IC 50 of 5 µM (Ali et al, 2017). Furthermore, the COX-2 pathway was inhibited using 50 µM and 100 ppm sargachromenol isolated from Sargassum micracanthum (Yang et al, 2013) and Iryanthera juruensis seeds (Silva et al, 2007), respectively. Here, the effect sizes of 70 and 84% found by Yang et al and Silva et al, respectively, are comparable with respect to the inhibition of the expression of COX-2 protein.…”
Section: Chromenolssupporting
confidence: 79%
“…Here, the effect sizes of 70 and 84% found by Yang et al and Silva et al, respectively, are comparable with respect to the inhibition of the expression of COX-2 protein. For the respective signaling molecule PGE 2 an IC 50 value of 30 µM was defined (Yang et al, 2013). In addition, inhibitory effects were observed for the expression of iNOS protein (95%) and the formation of nitric oxide (IC 50 82 µM) (Yang et al, 2013).…”
Section: Chromenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study on S. micracanthum related to anti-obesity [17] and anti-oxidation [5,10] has currently been conducted. In addition, Yang et al [28] reported that sargachromenol isolated from S. micracanthum showed anti-inflammatory activity by suppressing the activation of the NF-κB pathway in vitro, but they did not evaluate in vivo the antiinflammatory properties. In this study, the inhibitory effects of the ethanolic extract of S. micracanthum on inflammatory mediators in LPS-induced RAW 264.7 macrophages were evaluated in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%